2021
DOI: 10.1002/bmc.5118
|View full text |Cite
|
Sign up to set email alerts
|

Studies on effect of Tongfengxiaofang in HUM model mice using a UPLC–ESI–Q‐TOF/MS metabolomic approach

Abstract: Hyperuricemia (HUM) is a major risk factor for the development of gout. The traditional Chinese medicine (TCM) complex prescription Tongfengxiaofang (TFXF) is composed of a variety of TCMs. To study the therapeutic effect of TFXF on HUM mice and the mechanisms by which it exerts a therapeutic effect, the biochemical indices were measured and qPCR technique was used. In addition, plasma metabolomics analysis was carried out based on UPLC-Q-TOF/MS to evaluate the characteristics of the metabolic spectrum changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Another similar study investigated a mouse model of hyperuricemia by metabolomics. Chen et al (2021b) presented that Tongfengxiaofang could regulate various disorders of arginine biosynthesis, galactose metabolism, pyrimidine metabolism, glycerophospholipid metabolism, tryptophan metabolism, and TCA cycle caused by hyperuricemia. The potential molecular mechanisms of anti-hyperuricemia in other herbs, such as QZTBD, EMW, and chicory, have also been reported ( Chen et al, 2016 ; Bian et al, 2018 ; Huang et al, 2019 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…Another similar study investigated a mouse model of hyperuricemia by metabolomics. Chen et al (2021b) presented that Tongfengxiaofang could regulate various disorders of arginine biosynthesis, galactose metabolism, pyrimidine metabolism, glycerophospholipid metabolism, tryptophan metabolism, and TCA cycle caused by hyperuricemia. The potential molecular mechanisms of anti-hyperuricemia in other herbs, such as QZTBD, EMW, and chicory, have also been reported ( Chen et al, 2016 ; Bian et al, 2018 ; Huang et al, 2019 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…In this study, feeding HMEC did not result in any significant alterations in serum TG levels, implying the absence of adverse effects on lipid metabolism in dairy cows. Creatinine and urea serve as indicators of renal function [32]. Creatinine is primarily eliminated through glomerular filtration, and its levels predominantly reflect the glomerular filtration capacity [33].…”
Section: Discussionmentioning
confidence: 99%
“…These remarkably altered metabolites could be divided into a few main classes, such as amino acids and their metabolites, organic acids and their derivatives, fatty acids, nucleotides and their metabolites, benzene and substituted derivatives, and carbohydrates and their metabolites. Previous studies reported that HUA-induced CKD is usually accompanied by metabolic disorder, especially with respect to the metabolism of lipids, amino acids, and carbohydrates [44][45] . As shown in Fig.…”
Section: Effects Of Adbp On the Kidney Metabolome Of Huainduced Ckd Micementioning
confidence: 99%